Intrahepatic cholangiocarcinoma: The role of liver transplantation, adjunctive treatments, and prognostic biomarkers - Connor, Ashton A.; Kodali, Sudha; Abdelrahim, Maen; Javle, Milind M.; Brombosz, Elizabeth W.; Ghobrial, R. Mark (Frontiers in Oncology, 2022)
Intrahepatic cholangiocarcinoma (iCCA) is a primary epithelial cell malignancy of the liver with rising incidence rate globally. Its insidious presentation, heterogeneous and aggressive biology, and recalcitrance to current therapies results in unacceptably high morbidity and mortality. This has spurred research efforts in the last decade to better characterize it molecularly with translation to improved diagnostic tools and treatments. Much of this has been driven by patient advocacy. This has renewed interest in orthotopic liver transplantation (LT) with adjunctive therapies for iCCA, which was historically disparaged due to poor recipient outcomes and donor organ scarcity. However, the optimal use of LT as a treatment for iCCA care remains unclear. Here, we review the epidemiology of iCCA, the history of LT as a treatment modality, alternative approaches to iCCA local control, the evidence for peri-operative systemic therapies, and the potential roles of biomarkers and targeted agents. In doing so, we hope to prioritize areas for continued research and identify areas where multidisciplinary care can improve outcomes.